INTERACTIVE RADIO ON MONEY, FINANCIAL TECHNOLOGY, AND PSYCHOLOGY OF MONEY: SMART FINANCIAL MANAGEMENT IN THE MIDST OF A CRISIS - Renna Magdalena; Yanuar Dananjaya (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
The implementation of Community Service (Pengabdian Kepada Masyarakat/PKM) for December 2025 was carried out by a team from the Faculty of Economics and Business, Universitas Pelita Harapan Surabaya Campus, in collaboration with Radio Sangkakala Surabaya. The primary objective was to deliver broader financial education to the community by presenting qualified academic speakers from the Management and Accounting Study Programs. The activity was conducted in an interactive talkshow format under the overarching theme